## Answer :

1. Substitute [tex]\(x = -12\)[/tex] into the left-hand side of the equation:

[tex]\[ (-12)^2 + 10(-12) + 25 \][/tex]

2. Calculate each term:

[tex]\[ (-12)^2 = 144 \][/tex]

[tex]\[ 10(-12) = -120 \][/tex]

[tex]\[ 25 = 25 \][/tex]

3. Add these results together:

[tex]\[ 144 - 120 + 25 = 49 \][/tex]

4. Compare the left-hand side with the right-hand side of the original equation:

[tex]\[ 49 = 49 \][/tex]

Since both sides of the equation are equal when [tex]\(x = -12\)[/tex], we can conclude that [tex]\(x = -12\)[/tex] is indeed a solution to the equation [tex]\(x^2 + 10x + 25 = 49\)[/tex].

Thus, the correct answer is:

"Yes, because [tex]\((-12)^2 + 10(-12) + 25 = 49\)[/tex]."